Pengaruh Shopping Lifestyle, Discount, Dan Fashion Involvement Terhadap Impulse Buying E-Commerce Shopee (Studi Pada Masyarakat Desa Sengonagung Kec. Purwosari Kab. Pasuruan) - Putri Putu Samad; Abdul Kodir Djaelani; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research was conducted to determine the effect of Shopping Lifestyle, Discount, Fashion Involvement on Impulse Buying e-commers shoppe (a study in the community of Sengonagung village, Purwosari district, Pasuruan regency). This research uses explanatory research and a quantitative approach. The research sample was taken using purposive sampling technique with the Malhotra formula used to take the sample, namely the number of items x 5 so that the total sample is 100 respondents. To solve the problems in this study, using the validity test, reliability test, normality test, multiple linear regression test, multicollinearity test, heteroscedasticity test, classic assumption test. research using multiple linear regression analysis with the help of SPSS 22. The results of this study are the variables Shopping Lifestyle, Discount, Fashion Involvement simultaneously affect Impulse Buying, partially Shopping Lifestyle variables, and Fashion Involvement affect Impulse Buying. Meanwhile, the discount variable has no significant effect partially on impulse buying. Keywords: Shopping Lifestyle, Discount, Fashion Involvement, Impulse Buying